Beyond Attractions: The Role of Tour Operators in Crafting Unforgettable Tourist Experiences at the Destination - Kusumah Ahmad Hudaiby Galih (Budapest International Research and Critics University, 2023)
This study explores the role of tour operators in designing unique and unforgettable tourist experiences, emphasizing the need to consider more than just the attractions offered by a destination. It employs qualitative research methods, involving in-depth interviews with 12 tour operator managers to understand their approach in experience design. The findings suggest that tour operators employ three main strategies in itinerary planning: the selection of tourist attractions, designing variations, intensity, and sequences of visits, and managing guest expectations and perceptions. In attraction selection, a balance is struck between iconic landmarks, affordable alternatives, and hidden gems. Variations, intensity, and sequences of visits are orchestrated to prevent monotony, optimize the timing and duration of visits, and build towards a climactic end to the trip. Lastly, tour operators aim to exceed client expectations through unexpected upgrades, additional attractions, and small gifts. This research underscores the importance of a comprehensive and strategic approach in designing travel experiences, highlighting the pivotal role of tour operators. The findings have significant implications for tourism management entities, encouraging them to adopt a more holistic approach to enhance tourist satisfaction and create memorable experiences.